-15(w+8)-2(2w-60)=6

Simple and best practice solution for -15(w+8)-2(2w-60)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15(w+8)-2(2w-60)=6 equation:


Simplifying
-15(w + 8) + -2(2w + -60) = 6

Reorder the terms:
-15(8 + w) + -2(2w + -60) = 6
(8 * -15 + w * -15) + -2(2w + -60) = 6
(-120 + -15w) + -2(2w + -60) = 6

Reorder the terms:
-120 + -15w + -2(-60 + 2w) = 6
-120 + -15w + (-60 * -2 + 2w * -2) = 6
-120 + -15w + (120 + -4w) = 6

Reorder the terms:
-120 + 120 + -15w + -4w = 6

Combine like terms: -120 + 120 = 0
0 + -15w + -4w = 6
-15w + -4w = 6

Combine like terms: -15w + -4w = -19w
-19w = 6

Solving
-19w = 6

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Divide each side by '-19'.
w = -0.3157894737

Simplifying
w = -0.3157894737

See similar equations:

| (a+4)(a+49)=0 | | 11-7x=55-45x | | 48=.5(4)(8+b) | | 2x-17=x+2 | | 7x-6=7(x+2) | | 6x+5=9x-7 | | 242.36=29.3(5p-5) | | 9a+3b-4a+2b= | | 26=.5(4)(b+5) | | 163-7x=38x+23 | | 21g-7= | | 2(x+2)+4x=16 | | 8n-14=42 | | -5n=35 | | 18=12x-2x^2 | | 14-9x=184-44x | | n*3=n+6 | | 4x+24=-24 | | a=.5(6)(8+4) | | 3x+15=-95-7x | | 3(2t+8)=4(2+t) | | 3x-12-29=29-4x+7 | | -2(x+4)=-2x+9 | | 2x+3x-7=23 | | -10u+6=-8u-2 | | In(7x+8)=In(2x-22) | | 5(2r+23)-2=3 | | 3r+r=8 | | 9b+44=76 | | 36.7-42.42=42.42-x | | -36-2x=12-10x | | solveIn(7x+8)=In(2x-22) |

Equations solver categories